Parameter Optimization and Mechanism Analysis of Coordinated Adaptive Inertia-Damping Control for Virtual Synchronous Generator (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
Fixed-parameter virtual synchronous generator (VSG) control is subject to a trade-off between inertial support and damping performance under transient disturbances. To address this issue while avoiding the high computational cost of black-box optimization, this paper presents a deterministic parameter-optimization method for coordinated adaptive inertia-damping control. The post-disturbance response is first divided into acceleration andrecovery intervals according to the time-domain evolution of angular-frequency deviation and RoCoF, and a continuous piecewise adaptive law is then formulated to allocate virtual inertia and damping to the corresponding transient stages. An augmented root-locus analysis is used to determine the small-signal stability boundary of the adaptive coefficients. Within this boundary, the inertia and damping coefficients Kj and Kd are selected through a control-variable time domain simulation procedure. MATLAB/Simulink results show that the proposed method reduces active-power overshoot and improves frequency support under bidirectional step disturbances compared with fixed-parameter and single-parameter adaptive VSG controls. The proposed design has an explicitstability basis and a simple algebraic structure, making it suitable for digital implementation in converter-interfaced microgrids.
Keywords: Virtual Synchronous Generator (VSG), Coordinated Adaptive Control, Pa-rameter Optimization